2000
DOI: 10.1007/s100380070034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural studies of Japanese patients with sialidosis type 1

Abstract: To gain insight into the pathogenesis of sialidosis type 1, we performed molecular investigations of two unrelated Japanese patients. Both of them are compound heterozygotes for base substitutions of 649 G-to-A and 727 G-to-A, which result in amino acid alterations V217M and G243R, respectively. Using homology modeling, the structure of human lysosomal neuraminidase was constructed and the structural changes caused by these missense mutations were deduced. The predicted change due to V217M was smaller than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
5
21
1
Order By: Relevance
“…In vitro expression studies demonstrated that the mutant enzyme is targeted to the lysosome and retains about 10% of residual activity . Finally, the c.880C4T (p.R294S) mutation was found in two unrelated individuals of AfroAmerican origin affected with type I sialidosis [Bonten et al, 2000], and a combination of c.649G4A (p.V217M) and c.727G4A (p.G243R) mutations were found in two unrelated sialidosis type I patients from Japan [Naganawa et al, 2000]. All other missense mutations detected in the sialidase gene were individual (Table 1).…”
Section: Missense Mutationsmentioning
confidence: 91%
See 1 more Smart Citation
“…In vitro expression studies demonstrated that the mutant enzyme is targeted to the lysosome and retains about 10% of residual activity . Finally, the c.880C4T (p.R294S) mutation was found in two unrelated individuals of AfroAmerican origin affected with type I sialidosis [Bonten et al, 2000], and a combination of c.649G4A (p.V217M) and c.727G4A (p.G243R) mutations were found in two unrelated sialidosis type I patients from Japan [Naganawa et al, 2000]. All other missense mutations detected in the sialidase gene were individual (Table 1).…”
Section: Missense Mutationsmentioning
confidence: 91%
“…Using homology modeling, a potential effect of missense mutations on the sialidase tertiary structure was estimated and was correlated with the residual activity, folding, and intracellular localization of the enzyme, as well as with the clinical phenotype [Bonten et al, 2000;Lukong et al, 2000Lukong et al, , 2001Naganawa et al, 2000;Itoh et al, 2002]. For example, Lukong et al [2000] built the structural model of human sialidase using the atomic coordinates of homologous sialidases from Micromonospora viridifaciens, Salmonella typhimurium, and Vibrio cholerae.…”
Section: Missense Mutationsmentioning
confidence: 99%
“…Conservation of the basic structural fold of sialidases, which consists of six four-stranded antiparallel -sheets arranged as the blades of a propeller around an axis of symmetry passing through the active site, among various species has also been shown (Crennell et al 1993(Crennell et al , 1994Gaskell et al 1995), which makes it possible to model the tertiary structure of human lysosomal sialidase (Lukong et al 2000;Naganawa et al 2000). In the present study, we identified three new missense mutations resulting in amino acid substitutions, and characterized the mutant products biochemically.…”
Section: Introductionmentioning
confidence: 81%
“…Lysosomal sialidase cDNA, including the entire coding region, was obtained by reverse transcription (RT)-polymerase chain reaction (PCR), and the nucleotide sequence was determined according to a previous report (Naganawa et al 2000). As described in the Results section, 239C-to-T (P80L), 718T-to-C (W240R), and 946C-to-T (P316S) substitutions were detected in exons 2, 4, and 5, respectively, of the lysosomal sialidase gene.…”
Section: Gene Analysismentioning
confidence: 99%
See 1 more Smart Citation